On the Onset Delays of Solar Energetic Electrons and Protons: Evidence for a Common Accelerator - Strauss Roelf D.; Dresing Nina; Richardson Ian G.; van den Berg Jabus; Steyn Petrus J. (IOP Publishing Ltd, 2025)
The processes responsible for the acceleration of solar energetic particles (SEPs) are still not well understood, including whether SEP electrons and protons are accelerated by common or separate processes. Using a numerical particle transport model that includes both pitch-angle and perpendicular spatial diffusion, we simulate, among other quantities, the onset delay for MeV electrons and protons and compare the results to observations of SEPs from widely separated spacecraft. Such observations have previously been interpreted, in a simple scenario assuming no perpendicular diffusion, as evidence for different electron and proton sources. We show that, by assuming a common particle source together with perpendicular diffusion, we are able to simultaneously reproduce the onset delays for both electrons and protons. We argue that this points toward a common accelerator for these particles. Moreover, a relatively broad particle source is required in the model to correctly describe the observations. This is suggestive of diffusive shock acceleration occurring at large shock structures playing a significant role in the acceleration of these SEPs.